Multi-branched tubular components using water-assisted injection moulding - Nanjunda, Sachin (2019)
The development in automobile or consumer product industries is rising drastically. The complexity of the parts and limitations in design and manufacturing suppress the requirements of potential customers in production. The automotive or consumer products parts has become more and more complex with dimensional variations, curves, multi branches and connections especially using metals, results in higher production cost. Production of hollow plastic parts with complex geometries and several branches is a challenge for moulding industries. Water-assisted injection moulding (WAIM) technique provides a solution for these challenges when compared to the traditional injection moulding techniques. The primary objective of this work is to define new methods to produce hollow polymeric parts with several branches and complex geometries using computer simulations. We will study the WAIM process with different parameters and water injection approaches (i.e., using a single water injector and multiple water injector) and validate with experimental work. As this is a complex challenge, we have used computer simulations using Moldex3D software for the WAIM technique to optimise the operational parameters including the injection points for both plastic and water and additional gates to serve as a starting point for the experimental work and verification of the computer simulations. We use a standard water-assisted injection mould and machine as a test-bed to study the WAIM process to produce a branched tube with a diameter of 20 mm and a length of 315 mm, using both single injector and multi-injector systems. We will present the variation of the injection parameters and their influence on the final product quality. We have identified one mode of operation which leads to a substantial saving in the mass of plastic used to produce the parts. This innovative work will influence on the production of multi-branched and complex geometry hollow parts, which will effectively reduce the overall production time, raw material savings and eliminates the post-processing work on moulded polymeric parts.